IMPACT OF VILLAGE FUND ALLOCATION AND VILLAGE DEVELOPMENT PROGRAM ON COMMUNITY WELFARE - Maro, Yustina; Tang, Sefnat Aristarkus; Sabu, Junius Menase Sau (International Journal of Multidisciplinary Research and Literature, 2024)
Welfare is a condition where a person is safe, prosperous, safe from various kinds of problems or difficulties, and so on. This research aims to determine the impact of village fund allocation and village development programs on the welfare of village communities in South Mataru Village, Mataru District, Alor Regency with a population of village officials and South Mataru village communities and a sample of 56 people. Data was collected using a questionnaire while data analysis used classical assumption test research instruments and multiple linear regression using the t-test and F-test. The results of the study showed that the allocation of village funds partially affected the welfare of the people of South Mataru Village, Mataru District, and Alor Regency, which was proven. With a significance value of 0.000. Partially, the village development program influences the welfare of the people of South Mataru Village, Mataru District, Alor Regency, proven by a significance value of 0.000. Simultaneously, the allocation of village funds and village development programs has an effect on the welfare of the village community in Mataru Selatan Village, Mataru District, Alor Regency, which has been proven. With a significance value of 0.000